Budget impact analysis of use of aliskiren in hypertension on the Italian Health Care System - Zaniolo, Orietta; Pradelli, Lorenzo (Farmeconomia. Health economics and therapeutic pathways, 2009)
Cardiovascular (CV) disease management and prevention has been the leading cost driver in health care expenditures of industrialized Countries for many years, and this trend is not expected to change in the next future. Although drugs used for the treatment of arterial hypertension and heart failure account for three fourths of the total Italian pharmaceutical expenditures in this disease area, population studies indicate that only about half of all hypertensive patients are treated for this condition, and that, among treated individuals, only a minority achieves a satisfactory and stable blood pressure control. A complementary observation is that drug expenditures, as high as they seem to be, actually account for only about a fourth of the total direct cost of CV illness, as they are exceeded by costs of hospitalizations required for the acute management of the clinical events that should be, at least partially, prevented by the same cardiovascular drugs. An often pointed out corollary to these findings is that an increase in the rate of controlled hypertension in the population, although surely linked to a further increase in pharmaceutical expenditures, carries the potential to reduce overall health care costs for the management of CV patients. As far as drug treatment is concerned, there seem to be three applicable strategies capable of increasing blood pressure control rates, i.e. interventions directed toward the increase of the treated population, interventions aimed at improving compliance, and the introduction of innovative drugs to cover unmet needs. Aliskiren is the first agent of the new direct renin inhibitors drug class, and has been recently approved in Italy under strict reimbursement restrictions. In this paper, the Authors present a budget impact analysis in the perspective of the National Health Service, conducted by estimating eligible populations according to reimbursement limitations, calculating differential costs by patient subgroups and possible strategies (addition to vs substitution of ACE-Is or ARBs), and finally by applying expected market shares to the identified population. The low forecast market penetration (0.2% and 0.6% of eligible patients, in the first and second year, respectively) drives the results: the treatment of 3,274-9,821 patients induces a yearly increase of 1.5 to 4.5 million € with aliskiren added to ACE-Is or ARBs, and of 917,000 to 2,751,000 € in the substitution scenario.